2004
DOI: 10.1248/bpb.27.1986
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Caco-2/TC7 Cell Culture: Comparison between of Conventional 21-d and a Commercially Available 3-d System

Abstract: The Caco-2 cell model is a valuable tool for studying intestinal biotransformation of xenobiotics and to evaluate the potential of human intestinal absorption of new compounds. These properties were evaluated with Caco-2/TC7 cells in accelerated conditions to reduce maturation lag time from 21-d to 3-d in order to increase time and labor efficiency. Transmission electron and fluorescent microscopy were used for morphological characterization. Alkaline phosphatase and lactate dehydrogenase activities were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Secondly, the decrease of TEER values after day 20 (Fig. 2b) indicates a limited culture time, which is similar to Caco-2, and most probably caused by deterioration of tight junctions relative to the culture's age and initiated apoptosis (Da Violante et al 1994). …”
Section: Discussionmentioning
confidence: 85%
“…Secondly, the decrease of TEER values after day 20 (Fig. 2b) indicates a limited culture time, which is similar to Caco-2, and most probably caused by deterioration of tight junctions relative to the culture's age and initiated apoptosis (Da Violante et al 1994). …”
Section: Discussionmentioning
confidence: 85%
“…Calculation and Statistical Analysis The parameters of secondary structure of mucosal proteins, viz., a-helix (%), bsheet (%), b-turn (%), random coil (%) were obtained by simulating analysis from the Jasco J-700 software. Apical to basolateral apparent permeability (P app ) values of insulin across HIOEC monolayer were calculated with the equation according to Violante (2004), P app ϭdQ/dt/A/C 0 . Where dQ/dt is the rate of permeation, A is the diffusion area (cm 2 ), C 0 is the initial concentration of insulin in the donor compartment.…”
Section: )mentioning
confidence: 99%
“…Where dQ/dt is the rate of permeation, A is the diffusion area (cm 2 ), C 0 is the initial concentration of insulin in the donor compartment. 30) In order to compare the glucose-lowering effects of various treatments, the difference value of the area above the plasma glucose curve (DAAC) was calculated by the trapezoidal method. 31) All DAAC values were estimated versus the glucose level after insulin was sublingually administered in absence of any enhancer.…”
Section: )mentioning
confidence: 99%
“…Various studies were carried out; high seeding density, specific extracellular matrix composition and/or chemical addition in culture medium were shown to drastically decrease the Caco-2 differentiation period by 3-5 days (Alsenz and Haenel, 2003;Chong et al, 1997;Da Violante et al, 2004). However, comparison between conventional (21 days) and fast (3-7 days) culture methods revealed that the differentiation of Caco-2 and Caco-2/TC7 cells were not optimal (sub differentiated) with the faster protocol.…”
Section: Introductionmentioning
confidence: 99%
“…However, comparison between conventional (21 days) and fast (3-7 days) culture methods revealed that the differentiation of Caco-2 and Caco-2/TC7 cells were not optimal (sub differentiated) with the faster protocol. Furthermore, it appeared that the short protocol was unable to induce mature P-gp efflux (Liang et al, 2000;Da Violante et al, 2004). Despite the advantages associated with the fast culture protocols, the technique resulted in the generation of sub-optimal Caco-2 functional epithelium as compared with conventionally grown 21 day Caco-2 monolayers.…”
Section: Introductionmentioning
confidence: 99%